Augmented Reality Adoption Readiness in Islamic Education: A Comparative Study in MI Al Huda Kebonsari, Indonesia and Chariyathamsuksa School, Thailand - Wafiq, Habib Rachman; Prawidya Lestari; Aksorn, Asiyah (Borneo : Journal of Islamic Studies, 2025)
The integration of immersive technologies such as Augmented Reality (AR) presents unique opportunities and challenges for Islamic educational institutions. This research aims to fill this gap by conducting a multi-dimensional comparative analysis of AR adoption readiness at two Islamic educational institutions in Southeast Asia: MI Al Huda Kebonsari, Indonesia, and Chariyathamsuksa Foundation School, Thailand. Using a qualitative comparative case study approach, this study analyzes data from in-depth interviews, observations, and document analysis through a multi-layered analytical framework comprising the Education Technology Readiness Index (ETRI) for institutional capacity (macro), the Unified Theory of Acceptance and Use of Technology (UTAUT) for behavioral drivers (meso), and the Technology Readiness Index (TRI) for psychological dispositions (micro). The results reveal two distinct readiness profiles: MI Al Huda demonstrates a "policy-driven" readiness, characterized by a strong managerial vision but hampered by infrastructural resource limitations. Conversely, Chariyathamsuksa exhibits an "opportunity-driven" readiness, excelling in material resources due to external partnerships but facing challenges in institutionalizing innovation for long-term sustainability. This study concludes that true technological readiness is a complex socio-technical phenomenon, requiring simultaneous attention to infrastructure, perception, and mindset to ensure that technology is not only adopted but also wisely integrated to strengthen the core mission of Islamic education in shaping a generation of noble character.